KINETIC ISOTOPIC FRACTIONATION DURING CARBONATE DISSOLUTION IN LABORATORY EXPERIMENTS: IMPLICATIONS FOR DETECTION OF MICROBIAL CO2 SIGNATURES USING δ13C-DIC - Skidmore M.; Sharp M.; Tranter M. (My University, 2004)
Laboratory experiments on reagent-grade calcium carbonate and carbonate rich glacial sediments demonstrate previously unreported kinetic fractionation of carbon isotopes during the initial hydrolysis and early stages of carbonate dissolution driven by atmospheric CO2. There is preferential dissolution of Ca12CO3 during hydrolysis, resulting in δ13C-DIC values that are significantly lighter isotopically than the bulk carbonate. The fractionation factor for this kinetic isotopic effect is defined as εcarb. εcarb is greater on average for glacial sediments (−17.4‰) than for calcium carbonate (−7.8‰) for the < 63 μm size fraction, a sediment concentration of 5 g L−1 and closed system conditions at 5°C. This difference is most likely due to the preferential dissolution of highly reactive ultra-fine particles with damaged surfaces that are common in subglacial sediments. The kinetic isotopic fractionation has a greater impact on δ13C-DIC at higher CaCO3:water ratios and is significant during at least the first 6 h of carbonate dissolution driven by atmospheric CO2 at sediment concentrations of 5 g L−1. Atmospheric CO2 dissolving into solution following carbonate hydrolysis does not exhibit any significant equilibrium isotopic fractionation for at least ∼ 6 h after the start of the experiment at 5°C. This is considerably longer than previously reported in the literature. Thus, kinetic fractionation processes will likely dominate the δ13C-DIC signal in natural environments where rock:water contact times are short